Outcomes of pancreas retransplantation in patients with pancreas graft failure. Issue 13 (14th July 2018) - Gasteiger, S; Cardini, B; Göbel, G; Oberhuber, R; Messner, F; Resch, T; Bösmüller, C; Margreiter, C; Schneeberger, S; Maglione, M
Abstract: Background: Pancreas retransplantation is still a controversial option after loss of a pancreatic graft. This article describes the experience of pancreas retransplantation at a high-volume centre. Methods: This was a retrospective observational study of all pancreas retransplantations performed in a single centre between 1997 and 2013. Pancreatic graft loss was defined by the return to insulin dependence. Risk factors for graft loss as well as patient and graft survival were analysed using logistic and time-to-event regression models. Results: Of 409 pancreas transplantations undertaken, 52 (12·7 per cent) were identified as pancreas retransplantations. After a median follow-up of 65·0 (range 0·8–174·3) months, 1- and 5-year graft survival rates were 79 and 69 per cent respectively, and 1- and 5-year patient survival rates were 96 and 89 per cent. During the entire follow-up, 22 grafts (42 per cent) were lost. Patient survival was not associated with any of the donor- or recipient-related factors investigated. Five-year graft survival was better after simultaneous kidney–pancreas retransplantation than pancreas retransplantation alone: 80 per cent (16 of 20) versus 63 per cent (20 of 32) ( P = 0·226). Acute rejection (odds ratio 4·49, 95 per cent c.i. 1·59 to 12·68; P = 0·005) and early surgical complications (OR 3·29, 1·09 to 9·99, P = 0·035) were identified as factors with an independent negative effect on graft survival. Conclusion: Pancreas retransplantation may be considered for patients whose previous graft has failed. Abstract : Good outcome in selected patients